Biotin decorated PLGA nanoparticles containing SN-38 designed for cancer therapy. (3rd April 2017) - Mehdizadeh, Mozhdeh; Rouhani, Hasti; Sepehri, Nima; Varshochian, Reyhaneh; Ghahremani, Mohammad Hossein; Amini, Mohsen; Gharghabi, Mehdi; Ostad, Seyed Nasser; Atyabi, Fatemeh; Baharian, Azin; Dinarvand, Rassoul
Abstract: Active targeted chemotherapy is expected to provide more specific delivery of cytotoxic drugs to the tumor cells and hence reducing the side effects on healthy tissues. Due to the over expression of biotin receptors on cancerous cells as a result of further requirement for rapid proliferations, biotin can be a good candidate as a targeting agent. In this study, biotin decorated PLGA nanoparticles (NPs) containing SN-38 were prepared and in vitro studies were evaluated for their improved anti-cancer properties. In conclusion, biotin targeted PLGA NPs containing SN-38 showed preferential anticancer properties against tumor cells with biotin receptor over expression.